From good and service tax (GST) to sales and service tax (SST) / Shamsinar Rahman...[et.al.] - Rahman, Shamsinar; Johari, Nurul Aina; Abdul Manaff, Muhammad Izhuan; Wan Mohamad, Wan Sumayyah Syahidah; Ramli, Ramha Rozaili (Universiti Teknologi MARA Cawangan Pahang, 2019)
Tax is compulsory levy made by the government as a means of raising revenue and to finance government operations. Tax in general makes up about 80 percent of government revenue. The Malaysian government tax system is seen to revert to sales and service tax (SST) as compared to good and service tax (GST). This strategy is seen as part of government tax reform program to enhance the efficiency and effectiveness of the taxation system in Malaysia. The abolishment of GST as one of the promises make by Pakatan Harapan (PH) government. SST is not a new tax system for Malaysia since it has been implemented since 1970s and it was replaced with GST in 2015 under Dato Seri Najib administration. Therefore, this paper aim to discuss on both tax system which GST and SST and its political implication.